2015
DOI: 10.1021/am5082183
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Conductive Polypropylene Nanocomposites with Negative Permittivity at Low Carbon Nanotube Loading Levels

Abstract: Polypropylene (PP)/carbon nanotubes (CNTs) nanocomposites were prepared by coating CNTs on the surface of gelated/swollen soft PP pellets. The electrical conductivity (σ) studies revealed a percolation threshold of only 0.3 wt %, and the electrical conductivity mechanism followed a 3-d variable range hopping (VRH) behavior. At lower processing temperature, the CNTs formed the network structure more easily, resulting in a higher σ. The fraction of γ-phase PP increased with increasing the pressing temperature. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(83 citation statements)
references
References 96 publications
9
74
0
Order By: Relevance
“…[ 36 ] It therefore becomes independent of frequency in the percolation threshold, making lines connecting points measured at the same angular frequency cross. While this is true for homogeneous systems [ 83 ] and some heterogeneous composite systems, [ 49,58 ] our melt mixed samples showed a frequency-dependent values above the transition similar to that reported by Ratzsch et al [ 36 ] We chose to use the crossover of the 0.01 and 0.1 rad s −1 isolines, since it is the lower range of frequencies where the percolated zone was more easily observable experimentally.…”
Section: Rheological Behavior Of Ipp Nanocomposites In the Meltsupporting
confidence: 74%
See 2 more Smart Citations
“…[ 36 ] It therefore becomes independent of frequency in the percolation threshold, making lines connecting points measured at the same angular frequency cross. While this is true for homogeneous systems [ 83 ] and some heterogeneous composite systems, [ 49,58 ] our melt mixed samples showed a frequency-dependent values above the transition similar to that reported by Ratzsch et al [ 36 ] We chose to use the crossover of the 0.01 and 0.1 rad s −1 isolines, since it is the lower range of frequencies where the percolated zone was more easily observable experimentally.…”
Section: Rheological Behavior Of Ipp Nanocomposites In the Meltsupporting
confidence: 74%
“…[ 62 ] From this fi gure the strong effect of the carbon-based fi llers on the viscoelastic behavior of the poly(propylene) is evident. The pronounced effect is increasing G ′ by several orders of magnitude as reported for other iPP nanocomposites with CNTs, [ 7,44,45,51,[55][56][57][58] graphite, [ 61 ] and TrGO. [ 45,62 ] Figure 4 a shows a plateau in G ′ in composites with 10 wt% of CNTs at low frequencies, attributed to the formation of a percolated network within the nanocomposite limiting the polymer relaxations as above discussed.…”
Section: Rheological Behavior Of Ipp Nanocomposites In the Meltsupporting
confidence: 70%
See 1 more Smart Citation
“…It was found that the ɛ″ of the FGR-PR composites increased with increasing FGR content, indicating enhanced dielectric loss. Dielectric loss was mainly caused by interfacial polarization and conduction [45][46][47][48][49]. The interfacial polarization enhanced with the increasing FGR content, resulting in enhancement of interfacial polarization loss.…”
Section: Dielectric Properties Of the Fgr-pr Compositesmentioning
confidence: 99%
“…For example, after introducing 0.7 wt% polyaniline (PANI) functionalized multi-walled carbon nanotubes (MWCNTs) into epoxy matrix, an 85% improvement in the tensile strength was obtained [24]. The electrical conductivity of polypropylene (PP) was increased by~7 orders of magnitudes after incorporating 0.3 wt% CNTs [25]. Adding 40 wt% functionalized graphite nanoplatelets (fGNPs) into polyphenylene sulfide (PPS) leads to a 20 times higher thermal conductivity as compared to pure PPS [26].…”
mentioning
confidence: 99%